PELATIHAN PEMBUATAN LAPORAN KEUANGAN SEDERHANA BAGI PEMUDA DI DESA SANTUA SAWAHLUNTO SEBAGAI UPAYA PEMBEKALAN KETERAMPILAN WIRAUSAHA DAN PENGUATAN UMKM - Agus Nurofik; Sartika Yuliana; Wila Farlina; Nazirwan; Nadia Angraini (Bajang Institute, 2022)
: Young people who are classified as active youth, some of whom have the initiative to enter into micro-scale entrepreneurship. The enthusiasm of the entrepreneurial youth was followed up by the STIA Adabiah Community Service team by helping them overcome several problems that are generally experienced by businesses, especially in the field of financial reports. Therefore, this community service is carried out with the aim of helping to start a business in neat and correct financial records through the delivery of basic financial knowledge. The method chosen is by providing counseling and training. The results of this community service activity are practical and simple guidelines in the form of guidelines for micro businesses in making simple financial reports that are applied to Microsoft Excel which are summarized in the form of PKM STIA Adabiah material.